Draft genome sequence of Venturia carpophila, the causal agent of peach scab - Chunxian Chen; Clive H. Bock; Bruce W. Wood (Standards in Genomic Sciences, 2017)
Abstract Venturia carpophila causes peach scab, a disease that renders peach (Prunus persica) fruit unmarketable. We report a high-quality draft genome sequence (36.9 Mb) of V. carpophila from an isolate collected from a peach tree in central Georgia in the United States. The genome annotation is described and a phylogenetic analysis of the pathogen is presented. The genome sequence will be a useful resource for various studies on the pathogen, including the biology and ecology, taxonomy and phylogeny, host interaction and coevolution, isolation and characterization of genes of interest, and development of molecular markers for genotyping and mapping.